Local community in the era of social media technologies : a global approach - Titangos, Hui-Lan H.; ScienceDirect eBooks (Oxford ; Cambridge : Chandos Publishing, 2013)
Social media technologies can help connect local communities to the wider world. Local Community in the Era of Social Media Technologies introduces the experience of bringing a local community to the world. This book, with the model of Santa Cruz County, California, develops a truly global approach to the subject -- See more at: http://store.elsevier.com/product.jsp?isbn=9781843346968.
pt. 1. History: never a dull moment -- pt. 2. The era of library 1.0 -- pt. 3. Present: library 2.0 -- pt. 4. Social media for local community -- pt. 5. Future: library 3.0 and beyond.
Includes bibliographical references (pages 261-271) and index.
Print version record.
Safari Books Online
Elsevier
Keywords: Social media; Libraries and community; Online social networks -- Library applications; LANGUAGE ARTS & DISCIPLINES -- Library & Information Science -- General; Libraries and community; Online social networks -- Library applications; Social media; Internet, Web and Social Media; Social media; Electronic books